COMPARATIVE ASSESSMENT OF TOTAL COMBINING ABILITY EFFECTS OF SMOOTH BROME-GRASS SAMPLES USING POLY-CROSS METHOD AND DIALLEL ANALYSIS BY ELEMENTS OF FEED AND SEED PRODUCTIVITY - Marinich, L. H.; Barabolia, O. V.; Kavalir, L. V. (Scientific Progress & Innovations, 2021)
Breeding new varieties of smooth brome-grass for pasture and multiple-cutting use can be conducted by different ways, depending on selection tasks and achievements as well as the available original material. Hybridization is the most effective technique of creating the initial material in perennial grasses. The crossing of grasses in cross-pollinating crops takes place by two ways: at free cross-pollinating of specially chosen pairs under isolation conditions or by artificial pollination. During the recent years, the method of breeding complex-hybrid varieties-populations has been widely used in the selection of cross-pollinating crops. It is based on free cross-pollinating of selected components in the poly-cross seed field. The method is the least expensive and the most economical. The purpose of the research consisted in estimating the effects of the total combining ability of smooth brome-grass samples using poly-cross method and diallel analysis by the elements of feed and seed effectiveness. The studies were conducted in the experimental field of Poltava State Agricultural Station named after M. I. Vavylov of the Institute of Pig Breeding and Agro-Industrial Production of the National Academy of Agrarian Sciences of Ukraine. The collection of smooth brome-grass amounting 80 samples of various ecological and geographical origins became the study material. 5 samples of smooth brome-grass were used in crossing by the scheme of diallel analysis and poly-cross: Radio-mutant к-1 (UJ2000209), Radio-mutant к-5 (UJ2000210), Radio-mutant к-7 (UJ2000211), Anto (UJ2000206), and Poltavskyi 52 (UJ2000003). As a result of conducted crossings, hybrids between 5 collection samples by the complete diallel scheme in the amount of 20 combinations were obtained. Thus, five poly-cross hybrids were received: 0101, 0105, 0107, 0110, and 0152. The research results have shown that Poltavskyi 52 sample has higher total combining ability (TCA) effects by the structural elements of feed productivity (the number of vegetative-extending shoots, foliation, dry matter yield, protein content in dry matter), while the least TCA effects were typical for Radio-mutant к-5(by the elements of the number of vegetative-extending shoots and foliation) and Radio-mutant к-7 (by the elements of dry matter yield and protein content in dry matter). The highest TCA effects by the signs of seed productivity (the number of reproductive shoots, head length) were detected in Anto sample, while the least TCA effects by the mentioned signs were typical for Radio-mutant к-5 and Radio-mutant к-1.